Tafsir Hikayati as A Resistance Hermeneutics: Hikayat Prang Sabi’s Contribution to Holy War Literature and Quranic Studies - Fadhli, Fadhli; Ichwan, Moch Nur; Machasin, M. (Al-Jami'ah Research Centre, 2024)
This article will elaborate on the model of interpreting the Quran in Hikayat Prang Sabi. Guided by the text by Teungku Chiek Pante Kulu, the author analyses the data by Hans Georg Gadamer’s ideas about “Preunderstanding”, “Fusion of Horizons”, and “Historical Consciousness”. This research shows that Hikayat Prang Sabi has introduced a unique model of interpreting the Quran by adopting hikayat instruments in Acehnese culture. The author identifies this interpretation model in this research with Tafsir Hikayati. Tafsir Hikayati has contributed to constructing the Acehnese’s resistance to Dutch colonialism by bringing together two very influential spirits in Acehnese society: religion and culture. Through Tafsir Hikayati, Teungku Chiek Pante Kulu constructs a “Resistance Hermeneutics” by interpreting Islamic religious texts (the Quran) using the Acehnese cultural language (hikayat). Combining these two spirits has helped the Acehnese people accept and capture the message of resistance conveyed by Hikayat Prang Sabi so that it succeeded in awakening the spirit of ideological struggle against Dutch colonialism.[Artikel ini mengelaborasi model penafsiran Al-Quran dalam Hikayat Prang Sabi. Dengan berpedoman pada teks karya Teungku Chiek Pante Kulu, penulis menginterpretasi data dengan meminjam gagasan Hans Georg Gadamer tentang “Pra-Pemahaman”, “Perpaduan Horizon (cakrawala)”, dan “Kesadaran (keterpengaruhan) sejarah”. Penelitian ini menunjukkan bahwa Hikayat Prang Sabi telah memperkenalkan model penafsiran Al-Quran yang khas dengan mengadopsi intrumen hikayat dalam kebudayaan Aceh. Dalam penelitian ini, penulis mengidentifikasi model penafsiran tersebut dengan istilah Tafsir Hikayati. Tafsir Hikayati telah berkontribusi dalam mengkontruksi perlawanan orang Aceh terhadap kolonialisme Belanda dengan mempertemukan dua spirit yang sangat berpengaruh dalam masyarakat Aceh: agama dan budaya. Melalui Tafsir Hikayati, Teungku Chiek Pante Kulu mengonstruksi tafsir perlawanan (resistance hermeneutics) dengan melakukan interpretasi teks keagamaan Islam (Al-Quran) menggunakan bahasa kebudayaan (hikayat) yang berkembang di Aceh. Perpaduan dua spirit tersebut telah membantu orang Aceh dalam menerima dan menangkap pesan perlawanan yang disampaikan oleh Hikayat Prang Sabi sehingga berhasil membangkitkan semangat perjuangan ideologis dalam melawan penjajahan Belanda.]